The Issues and Solutions in Teaching English for Specific Purposes (ESP) To Adult Learners (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article reveals the teaching English for Specific Purposes (ESP) to adult learners presents a unique set of and requires tailored approaches to ensure effective learning outcomes. ESP aims to equip individuals with language skills relevant to their professional or academic fields. However, several issues commonly arise in this specialized teaching domain.